Burn the fat, feed the muscle : transform your body forever using the secrets of the leanest people in the world - Venuto, Tom (Harmony Books, 2013)
"A smart, energizing program to help you shed fat, build muscle, and achieve your ideal body in just 30 days! A huge success as a self-published ebook, Burn the Fat, Feed the Muscle is the bible of fat loss that will allow any reader to get his or her dream body. Tom Venuto has created a program using the secrets of the world's leanest people,although it's not about getting ripped; it is about maximizing your fat loss through nutrient timing and strategic exercise. This totally revised and 25% new book includes a never-before-shared plan that will make it even easier for readers to achieve amazing results"--